Religious socialization in Iranian Islamic girls schools - Jafari, Fakhereh Khatibi; Krauss, Steven Eric; Suandi, Turiman (Canadian Center of Science and Education, 2016)
Although Iran’s educational system is not secular in character, many Iranian parents prefer to send their children to private Islamic schools. It is widely assumed that such schools are more effective in socializing their students toward the Shiite worldview. To date, no known studies have been conducted to investigate the impacts of the Islamic schools’ formal and informal religious education on Iranian youths’ religious commitments and preferences. In short, this article focuses on how attending private Islamic schools in Iran impacts on the construction of students’ religious beliefs and attitudes. A qualitative, phenomenological methodology was employed with thirty former students of Islamic girl schools, aged 20 to 25 years old. Overall, the findings contrast somewhat with the existing literature by demonstrating that in most of our study participants, attending Islamic schools influenced future religious preferences and commitments by increasing unpleasant feelings and critical attitudes toward religion in general, and the Islamic-Shiite religious worldview specifically.